Allelopathic potential of Cymbopogon citratus over beggarticks (Bidens sp.) germination - Krenchinski, Fábio Henrique [UNESP]; Albrecht, Leandro Paiola [UNESP]; Albrecht, Alfredo Junior Paiola [UNESP]; Zonetti, Patrícia Costa [UNESP]; Tessele, Augusto [UNESP]; Barroso, Arthur Arrobas Martins [UNESP]; Placido, Henrique Fabricio [UNESP] (Southern Cross Publishing, 2017)
Allelochemicals are important and innovative tools for weed control as they neither harm the environment nor increase weed management costs. The secondary metabolites can be extracted by water or soaking and later applied in soil or leaves. This study evaluated the leaf extracts of Cymbopogon citratus, affecting germination of Bidens pilosa and B. subalternans seeds. Two trials were conducted in germination chambers. The completely randomized design was employed in both trials with 5 replications. Trial one was arranged in a 2×3 double factorial design, with two periods of leave collection (morning and afternoon); and three extract preparations (aqueous extract by maceration, aqueous extract by infusion and control with distilled water). Trial two was set up in a 2×2×5 triple factorial design, with two extracts (aqueous extract by maceration, aqueous extract by infusion); two time of day collection (morning and afternoon) and five extracts concentrations (0; 25; 50; 75 and 100%). The means were compared by F and Tukey's test (p ≤ 0.05). To evaluate extracts concentrations a regression analysis was run. The results showed that the aqueous extract by maceration of C. citratus decreased germination and germination speed of Bidens pilosa and Bidens subalternans more than the aqueous extract by infusion, for both species. The concentrations interfered, inversely and proportionally, decreasing germination and germination speed. The germination of beggarticks was affected by the extracts of C. citratus, suggesting further studies for this plant.
Keywords: Allelochemicals; Bidens pilosa; Bidens subalternans; Bioherbicides; Lemon grass